2020
DOI: 10.1111/bjh.17087
|View full text |Cite
|
Sign up to set email alerts
|

Circulating cell‐free DNA improves the molecular characterisation of Ph‐negative myeloproliferative neoplasms

Abstract: Genetic studies in patients with Philadelphia-negative myeloproliferative neoplasms (MPNs) are essential to establish the correct diagnosis and to optimise their management. Recently, it has been demonstrated that it is possible to detect molecular alterations analysing cell-free DNA (cfDNA) in plasma samples, which is known as liquid biopsy. We have assessed the molecular profile of a cohort of 107 MPN patients [33 polycythaemia vera (PV), 56 essential thrombocythaemia (ET), 14 primary myelofibrosis (PMF) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 31 publications
4
17
0
Order By: Relevance
“…After we excluded the irrelevant manuscripts based on the screening of their titles and abstracts ( n = 81), we examined the full texts of 33 manuscripts. Finally, after we applied the exclusion and inclusion criteria, 27 original articles were included in this review [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After we excluded the irrelevant manuscripts based on the screening of their titles and abstracts ( n = 81), we examined the full texts of 33 manuscripts. Finally, after we applied the exclusion and inclusion criteria, 27 original articles were included in this review [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…The analyzed studies investigated the levels of cell-free DNA ( n = 1), extracellular vesicles ( n = 7), microparticles ( n = 14) or circulating endothelial cells ( n = 5) levels in MPNs. Flow cytometry was by far the most employed method of detection ( n = 23) [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors confirmed that the sensitivity and accuracy were similar for both types of genetic material tested, with a similar mutational profile identified. However, the median VAF detected was significantly higher in ccfDNA than in DNA extracted from granulocytes (29% versus 25%, respectively) [ 29 ].…”
Section: Diagnosismentioning
confidence: 99%